Tricuspid Regurgitation – Medical Management and Evolving Interventional Concepts - Beckhoff, Frederik; Alushi, Brunilda; Jung, Christian; Navarese, Eliano; Franz, Marcus; Kretzschmar, Daniel; Wernly, Bernhard; Lichtenauer, Michael; Lauten, Alexander (Frontiers in Cardiovascular Medicine, 2018)
Severe tricuspid regurgitation (TR) is a complex condition of the right ventricle (RV) and tricuspid valve apparatus and is frequently associated with symptomatic heart failure and a significant morbidity and mortality. In these patients, left heart pathologies lead to chronic pressure overload of the RV, eventually causing progressive RV dilatation and functional TR. Therefore, TR cannot be considered as isolated heart valve disease pathology but has to be understood and treated as one component of a complex structural RV pathology and is frequently also a marker of an advanced stage of cardiac disease. In these patients, medical therapy restricted to diuretics and heart failure medication is frequently ineffective. Also, severe TR in the setting of advanced heart failure constitutes a high risk for cardiac surgery. Neither one of these treatment options has demonstrated a beneficial effect on long-term prognosis. The recent innovations in transcatheter technology led to efforts to develop interventional approaches to severe TR. Multiple innovative treatment concepts are currently under preclinical and clinical investigation to replace or repair TV function. However, up to date none of these approaches is established and there is still a lack of clinical data to support the efficacy of transcatheter TR treatment.